-5(8r+3)=-5(7r-5)

Simple and best practice solution for -5(8r+3)=-5(7r-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(8r+3)=-5(7r-5) equation:


Simplifying
-5(8r + 3) = -5(7r + -5)

Reorder the terms:
-5(3 + 8r) = -5(7r + -5)
(3 * -5 + 8r * -5) = -5(7r + -5)
(-15 + -40r) = -5(7r + -5)

Reorder the terms:
-15 + -40r = -5(-5 + 7r)
-15 + -40r = (-5 * -5 + 7r * -5)
-15 + -40r = (25 + -35r)

Solving
-15 + -40r = 25 + -35r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '35r' to each side of the equation.
-15 + -40r + 35r = 25 + -35r + 35r

Combine like terms: -40r + 35r = -5r
-15 + -5r = 25 + -35r + 35r

Combine like terms: -35r + 35r = 0
-15 + -5r = 25 + 0
-15 + -5r = 25

Add '15' to each side of the equation.
-15 + 15 + -5r = 25 + 15

Combine like terms: -15 + 15 = 0
0 + -5r = 25 + 15
-5r = 25 + 15

Combine like terms: 25 + 15 = 40
-5r = 40

Divide each side by '-5'.
r = -8

Simplifying
r = -8

See similar equations:

| 1(8+x)=7 | | 6c+11=2c+51 | | .5(x+8)=-5 | | 6-22(x+6)=2 | | 4x-7(-7-9)=42 | | 6(3+3m)=3(3m+3) | | x^2-8x=-102 | | 6b+9=5b+17 | | 2.5(6x-4)=10+(1.5+0.5x) | | -7+13=4+n | | (0-6)(2x+1)=0 | | 10a-3=6a+33 | | 16=2(x-1)-6 | | 5a^2-9ab+8a= | | .30x+.50= | | -4.5=5x-x-x | | .30x+.5= | | -10(s+4)=-62 | | 2x+2=11x-70 | | 32+2+2=3.2 | | 2(f-1)=-4 | | x+2-3x=-8 | | 12y^6-16y5/4y^2 | | 11y+6=10y+8 | | 6x+4+4x+8=px+3 | | (3b+4b)(b-3)= | | 3(t+3)=-8 | | .30x+.05= | | 3-x=-2x-7 | | -48+n=14 | | 5(5c-1)-2=23c+5 | | -8y+4= |

Equations solver categories